Preceptoria na estratégia saúde da família: Percepção, formação e vivência. - Lima Neto, Pedro Joaquim de (2016)
The proposals of the National Curriculum Guidelines of health programs imply the need to discuss in depth the preceptorship and the preceptor training, a professional who transits between the teaching and the work. The objective was to analyze the preceptorship exercise in the supervised phase in the program of undergraduate in nursing. It is based on a descriptive and exploratory research, with qualitative approach, with the realization of a foc4al group for the data collection with nurses preceptors. For the data analysis the discourses were organized from the thematic analysis of content technique. Between the perceptions that surround the preceptorship is the accompaniment, supervision, orientation, besides the possibility of being example, to exchange knowledge and to renew professionally. The formation comprised the central debate to strengthen the preceptorship, being directed with the possibility of training in the own space of the undergraduate, university extension, work groups for the evaluation and planning of the students practices in the Institutions of Higher Education (IES), Postgraduate programs, PET / Health and working groups linked to the health-School System construction. Finally, three elements are conditions for the execution of the preceptorship with quality: overcoming the biomedical paradigm; Strengthening teaching-service integration; And pedagogical training for the exercise of preceptorship practice.